Spirituality of Catholic Teachers in Realizing Multicultural Education in Indonesia - Mathias Jebaru Adon (Millah: Journal of Religious Studies, 2021)
The spirituality of Catholic teachers is critical, considering that the Indonesian nation is rich in cultural, religious, ethnic, and racial diversity. If not managed, the diversity can lead to problems such as racism, radicalism, and others. This study aims to implement multicultural understanding among Catholic teachers by developing multicultural attitudes. This study uses library research by analyzing previous works on Catholic teachers and multicultural education in Indonesia. The results show that many efforts have been implemented to enhance multicultural education in Indonesia. Furthermore, Catholic teachers are required to be professional in teaching and have a spirituality that was derived from the Catholic faith. This spirituality should always be developed and maintained by realizing Catholic teachers’ status as pastoral agents, educators, apostles, and catechists. The formation of the multicultural character of Catholic teachers starts from inculcating multicultural values and fostering the Catholic faith for prospective Catholic teachers. Prospective Catholic teachers should be prepared to live and become the frontrunner in multicultural education by providing them with proper capacity in interreligious dialogue, comparative philosophy of religion, the study of local wisdom of Pancasila, and contextual theological studies. Prospective Catholic teachers are expected to encourage their future students’ national characters to create an inclusive Indonesian society.